Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5171/2017.761672
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organizational Culture on Employee Engagement in Saudi Banks

Abstract: The Saudi Banking industry is an important component of Saudi Arabia Economy. In the view of the high volume of business activities, Saudi Banks are keen to encourage employee participation and employee engagement. These behaviours will help banks in managing their business activities and business development. This paper provides a stimulating opportunity to advance the knowledge of the link between organizational culture, and employee engagement, at Saudi banks. This research paper will investigate the organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 26 publications
(33 reference statements)
3
23
0
3
Order By: Relevance
“…These results are consistent and support the idea of (Riyanto & Ali, 2017); (Bayasgalan, 2017); (Ilyasa et al, 2018). (Kalia & Verma, 2017); (Shehri et al, 2017); and (Meng & Berger, 2018). Which states, organization clture has a positive and significantly influence on employee engagement.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are consistent and support the idea of (Riyanto & Ali, 2017); (Bayasgalan, 2017); (Ilyasa et al, 2018). (Kalia & Verma, 2017); (Shehri et al, 2017); and (Meng & Berger, 2018). Which states, organization clture has a positive and significantly influence on employee engagement.…”
Section: Discussionsupporting
confidence: 87%
“…Kalia and Verma (2017) conducted a study on organizational culture and employee engagement among hospitality sector employees and found that Organizational culture is an important factor that promotes employee engagement (Kalia & Verma, 2017). According to Sehri et al (2017), Islamic culture has an influence on employee engagement (Shehri, Mclaughlin, & Al-ashaab, 2017). Supportive organizational culture demonstrates a strong, positive, significant direct effect on work engagement.…”
Section: The Effect Of the Organizational Culture On The Employee Engagementmentioning
confidence: 99%
“…Previous research has revealed that highly engaged employees are regarded as assets to the organization and serve as a reference point for retaining a talented and experienced workforce. In contrast, disengaged employees are considered ones who burden the organization, bringing about training costs, lower profitability, and absenteeism (Al Shehri et al, 2017). An engaged employee is considered emotionally attached to the organization, passionate about their work, and prioritizes the organization's success (Seijts & Crim, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Aftab et al (2012) concentrated on employee's role based performance. Other studies, which concentrated on employee performance, are Al Shehri et al (2017) and Awadh and Alyahya (2013). This study however, uses general dimension to measure performance.…”
Section: Research Hypothesesmentioning
confidence: 99%